Gender differences in the use of primary prevention ICDs in New Zealand patients with heart failure. Issue 1 (13th January 2018) - Looi, Khang-Li; Sidhu, Karishma; Cooper, Lisa; Dawson, Liane; Slipper, Debbie; Gavin, Andrew; Lever, Nigel
Abstract : Objective: Women have been under-represented in randomised clinical trials for primary prevention implantable cardioverter defibrillators (ICDs), and there are concerns about the efficacy of devices between genders. Our study aimed to investigate gender differences in the use of primary prevention ICD in patients with heart failure from the northern region of New Zealand. Methods: Patients with heart failure with systolic dysfunction who received primary prevention ICD/cardiac resynchronisation therapy-defibrillator (CRT-D) in the northern region of New Zealand from 1 January 2007 to 1 June 2015 were included. Complications, mortality and hospitalisation events were reviewed. Results: Of the 385 patients with heart failure implanted with ICD/CRT-D, women comprised 15.1% (n=58), and no change in utilisation of these devices was observed over the study period among women. Women were more likely to have non-ischaemic cardiomyopathy and have higher perioperative complications (8.6% vs 2.5%, P=0.02), with non-significant higher trend towards increased lead displacement (5.2% vs 1.8%, P=0.12). Women appeared to have lower all-cause (10.3% vs 18.7%, P=0.12), cardiovascular (5.2% vs 11.9%, P=0.13) and heart failure (3.5% vs 7.9%, P=0.22) mortalities but was not statistically significant. There were no gender differences in all-cause (70.7% vs 67%, P=0.58) or heart failure (19% vs 25%, P=0.32) readmissions. Conclusion: Perioperative complications were significantly more common in women referred for ICD/CRT-D. Although there has been a significant increase in ICD implantation rates, gender differences in the use of these devices still exist in New Zealand, in keeping with the demographics of ischaemic heart disease and systolic dysfunction between genders.